2015
DOI: 10.1186/s12970-015-0093-8
|View full text |Cite
|
Sign up to set email alerts
|

Plausible ergogenic effects of vitamin D on athletic performance and recovery

Abstract: The purpose of this review is to examine vitamin D in the context of sport nutrition and its potential role in optimizing athletic performance. Vitamin D receptors (VDR) and vitamin D response elements (VDREs) are located in almost every tissue within the human body including skeletal muscle. The hormonally-active form of vitamin D, 1,25-dihydroxyvitamin D, has been shown to play critical roles in the human body and regulates over 900 gene variants. Based on the literature presented, it is plausible that vitam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
134
0
23

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(163 citation statements)
references
References 115 publications
6
134
0
23
Order By: Relevance
“…The inability of the authors to document any beneficial effect of vitamin D on athletic performance may be due the fact that the participants of their study were not vitamin D deficient. It has been shown that the beneficial effects of vitamin D supplementation take place in individuals with significant vitamin D deficiency [158]. The lack of any beneficial effect of vitamin D supplementation was also reported in another study involving football players [215].…”
Section: Vitamin D Supplementation and Athletesmentioning
confidence: 83%
See 2 more Smart Citations
“…The inability of the authors to document any beneficial effect of vitamin D on athletic performance may be due the fact that the participants of their study were not vitamin D deficient. It has been shown that the beneficial effects of vitamin D supplementation take place in individuals with significant vitamin D deficiency [158]. The lack of any beneficial effect of vitamin D supplementation was also reported in another study involving football players [215].…”
Section: Vitamin D Supplementation and Athletesmentioning
confidence: 83%
“…It should be noted here that the baseline vitamin D levels of the majority soccer players in this study were deficient. Therefore the proposed mechanism by Dahlquist et al [158] was not applicable in this study. The authors suggest that other factors apart of vitamin D levels play a pivotal role including their initial training status.…”
Section: Vitamin D Supplementation and Athletesmentioning
confidence: 84%
See 1 more Smart Citation
“…119 Vitamin D supplementation has moreover been demonstrated to augment athletic performance in vitamin D-deficient athletes. 100 Early studies on collegiate athletes and students showed that cardiovascular fitness, muscle endurance and speed were enhanced following exposure to ultraviolet radiation.…”
Section: Effect Of Vitamin D Supplementation On Athletic Performancementioning
confidence: 99%
“…Investigation on the relationship between Vitamin D levels to athletic performance were evaluated by another study and showed that Vitamin D may improve athletic performance in vitamin D deficient athletes [6]. A second recent study evaluated the plausible ergogenic effects of vitamin D on athletic performance and recovery concluded that doses exceeding the recommendations for vitamin D could aid athletic performance [12].…”
mentioning
confidence: 99%